A framework for the systematic design of fed‐batch strategies in mammalian cell culture. Issue 12 (21st October 2014) - Kyriakopoulos, Sarantos; Kontoravdi, Cleo
ABSTRACT A methodology to calculate the required amount of amino acids (a.a.) and glucose in feeds for animal cell culture from monitoring their levels in batch experiments is presented herein. Experiments with the designed feeds on an antibody‐producing Chinese hamster ovary cell line resulted in a 3‐fold increase in titer compared to batch culture. Adding 40% more nutrients to the same feed further increases the yield to 3.5 higher than in batch culture. Our results show that above a certain threshold there is no linear correlation between nutrient addition and the integral of viable cell concentration. In addition, although high ammonia levels hinder cell growth, they do not appear to affect specific antibody productivity, while we hypothesize that high extracellular lactate concentration is the cause for the metabolic shift towards lactate consumption for the cell line used. Overall, the performance of the designed feeds is comparable to that of a commercial feed that was tested in parallel. Expanding this approach to more nutrients, as well as changing the ratio of certain amino acids as informed by flux balance analysis, could achieve even higher yields. Biotechnol. Bioeng. 2014;111: 2466–2476. © 2014 Wiley Periodicals, Inc.